The Suitability of Arabic Textbooks Curriculum 2013 for Fifth Graders of Madrasah Ibtidaiyah - Baiturrahman, Baiturrahman; Hasbullah, Akbar Al Fahmy (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2024)
To achieve  the  goal  of  the  Country    through  education,  textbooks  especially Arabic should be in line with the curriculum that is implemented. About textbook quality, the components of the textbook standard has been developed by National Agency of Education Standards (BSNP) initiated the textbook analysis. This article aimed to find suitability and discrepancy of the contents of Arabic textbooks for fifth graders in Madrasah Ibtidaiyah (Islamic Elementary School) adjusted to the standards set by BSNP. This type of research was content analysis. Meanwhile, in examining the data, descriptive analysis and content analysis were used. Primary data were obtained from Arabic language textbooks and secondary data were obtained from supporting sources such as books and journals. The feasibility of the contents of the Arabic textbook for fifth graders in Madrasah Ibtidaiyah by Sri Sabbahatun on the feasibility aspect of presentation based on motivation generators are available in the form of vocabulary illustrations that are appropriate to the topic of study and students practice the material presented to their group mates so that the class became interactive. Meanwhile, in terms of linguistic feasibility, the language used in mufradat and examples can be practiced by students. The integrated reading in each chapter is quite logical and simple so students can understand it. Among three aspects studied, namely the feasibility of content, presentation and language, it was stated that this Arabic book by Sri Sabbahatun was suitable for use.